An Educational Approach to the Concept of the Ruh in the Qur’an through the Character of Meri in the Jumbo Animated Movie - Hanifa, Millata; Muttaqin, Royhan Imamul; Fitri, Alifa Nur; Nuha, Ahmad Ulin; Auliya, Mustafida (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2025)
This research aims to examine the educational approach in conveying the concept of the ruh according to the Qur'an through the character Meri in the Jumbo animated movie. The concept of the ruh is an important part of Islamic teachings that is often difficult for children to understand due to its abstract and metaphysical nature. The animated Jumbo movie is considered a potential medium for conveying spiritual values in an engaging and communicative manner. The method used in this research is descriptive qualitative with a content analysis approach. Data were obtained from the narration of scenes in the Jumbo movie and verses from the Qur'an that are relevant to the concept of the ruh. The research results show that the character Meri depicts a spiritual journey and a quest for identity that symbolically represent the meaning of the ruh in Islam. This movie conveys values such as self-awareness, the meaning of life and the relationship with God in a subtle yet profound manner. An educational approach based on animated media like Jumbo can be a strategic alternative in teaching spiritual values. These findings open up opportunities for the development of more creative and contextual religious learning media, as well as providing a foundation for further research in the fields of Islamic education, child psychology and visual media.